PENGARUH LEVERAGE, PERTUMBUHAN PERUSAHAAN, PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERDAGANGAN GO PUBLIC - Titik Purwanti (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study is to determine the effect of leverage, company growth, profitability on firm value in publicly traded companies (listed on the IDX for the 2018-2020 period). This research is a quantitative descriptive research. The population in this study are all publicly traded companies on the IDX. The sampling technique used purposive sampling technique with a total sample of 28 companies. The data analysis technique used multiple linear regression test, t test, and F test. The results showed that partially showed that partially showed that leverage and profitability had no significant effect on firm value, while firm growth had a significant effect on firm value. The variables of leverage, firm growth and profitability have a significant effect on firm value. So the model used is in accordance with the goodness fit model, with an effect of 38.6%. While the remaining 61.4% is explained by other variables outside the research model, this is evidenced by the results of the coefficient of determination test.